Metrology and instrumentation practical applications for engineering and manufacturing - Mekid, Samir (Wiley-ASME Press series, 2021)
Metrology is the science and study of providing accurate measurements. It has relevance to mechanical, industrial, electrical, and quality engineering and is a foundational concept for the manufacturing industry, where the accurate calibration of measurements can have direct impact on a product's end quality and production cost. While metrology has historical roots that date back to the late-18th century, its modern applications remain relevant to the Industry 4.0 technologies of today.